FINANCIAL DETERMINANTS OF ENTREPRENEURSHIP IN NIGERIA - Precious Adukwu; Hyeladi Stanley Dibal (Gusau Journal of Accounting and Finance)
Finance is a crucial component to entrepreneurial success and the dearth of financial resources can be detrimental to entrepreneurs and affect entrepreneurial activities and growth opportunities. This study investigates the financial determinants of entrepreneurship in Nigeria from 1991 to 2021 using the auto regressive distributed lag model. The findings to the study revealed that while foreign direct investments and financial development negatively affect self-employment rate in Nigeria, access to finance increases the rate of self-employment in Nigeria. This study, therefore, recommends that policy makers need to make access to financial resources easier and at a lesser cost to individuals who wants to be self-employed in order to encourage self-employment and entrepreneurial activities for economic growth and stability.